Busy. Please wait.

show password
Forgot Password?

Don't have an account?  Sign up 

Username is available taken
show password


Make sure to remember your password. If you forget it there is no way for StudyStack to send you a reset link. You would need to create a new account.

By signing up, I agree to StudyStack's Terms of Service and Privacy Policy.

Already a StudyStack user? Log In

Reset Password
Enter the associated with your account, and we'll email you a link to reset your password.

Remove Ads
Don't know
remaining cards
To flip the current card, click it or press the Spacebar key.  To move the current card to one of the three colored boxes, click on the box.  You may also press the UP ARROW key to move the card to the "Know" box, the DOWN ARROW key to move the card to the "Don't know" box, or the RIGHT ARROW key to move the card to the Remaining box.  You may also click on the card displayed in any of the three boxes to bring that card back to the center.

Pass complete!

"Know" box contains:
Time elapsed:
restart all cards

Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

  Normal Size     Small Size show me how


Solving Equations by the Quadratic Formula and Quadratic Methods

Use the quadratic formula to solve this equation. d^2 + 7d -8 = 0 Since the eqaution is in standard form, substitute values of a, b, and c into the quadratic fthe ormula. Thus, d= (-(1) +/- sqaure root ((7^2) - 4(1)(-8))/ 2(1). Multiply. Then, simplify the sqaure root to get the solutions d= -8 and 1.
Use the quadratic formula to solve this equation. 1/2x^2 + 5x -1 = 0 Clear the equation of fractions by multiplying both sides of the equation by the LCD 2. Substitute the values of a, b, and c into the quadratic formula and solve. The solutions for x are -5 +/- 3* the sq.rt. of 3.
Solve. p^4 - 1296 = 0 Factor the binomial into two binomials since this equation is the difference of two squares. Thus, the equation becomes (p^2 - 36)(p^2 + 36) = 0. Set each factor to 0 and solve for p. The solutions are 6, -6, 6i, -6i.
Solve. x^2/3 - 2x^1/3 - 15 = 0 Substitute the variable u in the original equation for x^1/3. The equation becomes u^2 - 2u - 15 = 0. Solve for u by factoring the equation. Thus, u = 5 or u = -3. Since x^2/3 = (x^1/3)^2, substitute x^1/3 back in for the variable u. x = 125, x = -27
Solve. (2n + 1)^2 + 7(2n + 1) - 8 = 0 Substitute variable y in where there is a (2n+1) since it is repeated. The equation becomes y^2+7y-8=0. Factor the equation (y+8)(y-1)=0. Set each factor to 0. Solve for y. y= -8 or 1. Sub in (2n+1) back for the variable y and solve for n. n= -9/2 and 0
Find all real and complex roots. x^4 - 19x^2 + 48 = 0 First, sub in a linear term for the variable raised to the lowest power. Let y=x^2; y^2=x^4. The new equation is y^2-19y+48=0. Factor. (y-16)(y-3)=0. Set factors to 0. y=16 or 3. Sub x^2 back for variable y to find the original value, x. x=+/-4; +/- sqrt3
Solve. y^3 + 25y -3y^2 - 75 = 0 Factor by grouping. Group so that each group has a common factor. (y^3+25y)-(3y^2-75)=0. Factor out the GCF from each group. y(y^2+25)-3(y^2+25)=0. Factor out common factor (y^2+25). (y-3)(y^2+25)=0. Set factors to 0. Solve for y. Solutions are y=3; +/-5i
Created by: a0644929